2019
DOI: 10.30829/tar.v26i1.410
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Islamic Values in English Learning at Madrasah Ibtidaiyah Teacher Training Program (Pgmi) Uin North Sumatera

Abstract: This study aimed to find out: (1) HowEnglish Language Teaching Materials were; (2) How  the Concept of Islamic Values in English Language Teaching Materials was; and (3) How to integrate Islamic values in English teaching materials at the Madrasah Ibtidaiyah Teacher Training program (PGMI) at UIN North Sumatra. This research was library research which is one type of qualitative research. The fundamental characteristic in this study was that the data studied was written literature in the form of documents namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The challenge would raise a tension since the subject being taught was not easy to be situated with Islamic values. Rambe and Salminawati (2019) find that there has been a conflicting situation on English teaching in Islamic schools since there is a view that learning English as the target language which is totally different from students' cultural norms. This phenomenon influences the effort of integrating Islamic values at EFL teaching.…”
Section: The Challenge Of Integrating Islamic Messages In Eltmentioning
confidence: 99%
“…The challenge would raise a tension since the subject being taught was not easy to be situated with Islamic values. Rambe and Salminawati (2019) find that there has been a conflicting situation on English teaching in Islamic schools since there is a view that learning English as the target language which is totally different from students' cultural norms. This phenomenon influences the effort of integrating Islamic values at EFL teaching.…”
Section: The Challenge Of Integrating Islamic Messages In Eltmentioning
confidence: 99%
“…For EFL teachers, the challenge would raise a tension since the subject being taught was not easy to be situated with Islamic values. Rambe & Salminawati (2019) found that there has been a conflicting situation on English teaching in Islamic schools since there was a view that learning English as the target language which is totally different from students' cultural norms. There was common stereotyping that English is oriented to world life and does not give any benefits to their afterlife (Irfani, Meisuri, & Rohmatilah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lecturers and students can gain fruitful benefits from the use of some learning applications as part of educational technologies to take into hand this conflicting situation in English language teaching, which is totally different from students' cultural norms which they must have in distance learning (Rambe & Salminawati, 2019). There have been formerly several studies related to E-learning implementation in English language teaching across the globe, such as in China (Chai, 2012), Ghana (Arkorful & Abaidoo, 2014), Thailand (Saeheng, 2017), and Saudi Arabia (Mutambik, 2018).…”
Section: Introductionmentioning
confidence: 99%